Neural correlates of gait during overground and treadmill walking : an fNIRS study - Chai, Keller Xin Yu (Nanyang Technological University, 2021)
Walking while performing a cognitive task is a norm of daily living. Carrying out both tasks at once leads to deteriorations in one or both tasks as a result of competition for a limited pool of cognitive resources. However, this impairment in task performance is not equal between treadmill and overground walking modalities, and it remains unclear what the underlying cause of this inconsistency is. This study aimed to investigate the neural correlates of gait and differences in task prioritisation between both walking modalities. 30 healthy young adults (16 females; mean age: 25.6 years ± 2.67) were recruited for this study. Individuals were excluded if they had a neurological, musculoskeletal, or gait disorder, and were also excluded if they had lower limb or head injuries requiring surgery or hospitalisation within the past 6 months. This study used a randomised, counterbalanced crossover study design. Participants were randomly allocated into one of two sequences, and performed a walking task, a cognitive task, or both tasks at once on both walking modalities. Gait parameters were measured using inertial measurement unit sensors, and cortical activity was recorded with functional near-infrared spectroscopy. Results showed that dual-task walking performance deteriorated during overground walking only. No cognitive performance deteriorations were observed for either walking modality. Higher cortical activations, especially in the dorsolateral prefrontal cortex, were elicited during treadmill walking. In conclusion, these findings suggests that motor control strategies differ across walking modalities.